2018
DOI: 10.1371/journal.pone.0192636
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of -1562C>T polymorphism in the MMP9 gene with primary glaucoma in a north Indian population

Abstract: MMP (Matrix metalloproteinase) 9 is reported to affect glaucoma pathogenesis by altering intraocular pressure (IOP) through its role in remodeling the extracellular matrix (ECM) in the trabecular meshwork. A genetic variant at the promoter region in the MMP9 gene (-1562C>T) has a putative role in regulating its transcription rate and hence can affect genetic predisposition to primary glaucoma. The present study examined the association of -1562C>T promoter polymorphism in the MMP9 gene with Primary Open Angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(47 reference statements)
0
11
0
1
Order By: Relevance
“…Role of matrix metalloproteinase‐9 (MMP‐9) variants have been well investigated in different populations as MMP‐9 gene is responsible for remodeling of extracellular matrix. A recent study in North Indian patients showed 1.6 and 1.4 fold higher risk for development of PACG and POAG, respectively, in subject harbored with mutant for MMP‐9 (−1562 C > T) polymorphism . Meta‐analysis if earlier published reports revealed protective feature of rs17576 and rs3918249 variant against glaucoma development .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Role of matrix metalloproteinase‐9 (MMP‐9) variants have been well investigated in different populations as MMP‐9 gene is responsible for remodeling of extracellular matrix. A recent study in North Indian patients showed 1.6 and 1.4 fold higher risk for development of PACG and POAG, respectively, in subject harbored with mutant for MMP‐9 (−1562 C > T) polymorphism . Meta‐analysis if earlier published reports revealed protective feature of rs17576 and rs3918249 variant against glaucoma development .…”
Section: Introductionmentioning
confidence: 92%
“…A recent study in North Indian patients showed 1.6 and 1.4 fold higher risk for development of PACG and POAG, respectively, in subject harbored with mutant for MMP-9 (−1562 C > T) polymorphism. 11 Meta-analysis if earlier published reports revealed protective feature of rs17576 and rs3918249 variant against glaucoma development. 12,13 In Han Chinese population, variants of rs3918254 were associated with susceptibility to PACG.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset contains the raw data (supplementary Table), frequencies of alleles and genotypes ( Table 1 ) for three SNPs of two MMP genes (rs1799750 MMP1 , rs3918242 and rs17576 MMP9 ) in Russian patients diagnosed with POAG, EH, and PU. These polymorphisms were previously reported for their association with POAG, EH, and PU ( Table 2 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . The studied SNPs manifest the regulatory potential ( Table 3 ), which is evidenced by several eQTLs ( Table 4 ) and splicing QTLs ( Table 5 ).…”
Section: Data Descriptionmentioning
confidence: 87%
“…Awadalla, et al [20], describe in Caucasians an amino acid change (Arginine to Glutamine) responsible for protein expression of MMP9 favorable to glaucoma with SNPs rs17576 and rs3918249. In addition, Thakur, et al [21] highlight the relationship between the change in MMP9 activity in the retina, the optic nerve, the aqueous humor, the trabeculum and glaucoma in the human eye. In the Chinese, the most likely locus for angle-closure glaucoma is rs3918254.…”
Section: Discussionmentioning
confidence: 99%